(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article is about a problem, a mathematical problem, that solving a problem develops logical thinking, a broad worldview, creative initiatives, understanding, intelligence, sensitive abilities and creates practical and necessary skills and competencies in them, the abstractness of mathematical problems, the logic of their form and content. information is given that it is different from the problems of other sciences due to its connection and the unique complexity of the method of solving, that the solving of such problems has attracted the attention of scholars for centuries, and that they have left wonderful opinions about the problem and its essence.